2020
DOI: 10.1021/acs.macromol.0c00311
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Free Click Polymerization of Thiol and Activated Internal Alkynes: A Facile Strategy toward Functional Poly(β-thioacrylate)s

Abstract: Thiol–yne click polymerizations have become efficient synthetic tools for the construction of linear and hyperbranched polysulfides with advanced functionalities. However, the polymerization reaction of internal alkynes and thiols has been rarely utilized to prepare functional polymers. In this work, a catalyst-free click polymerization between activated internal alkyne and thiol was developed. The polymerizations of 4,4′-thiodibenzenethiol (1) with dibutynoates (2) and diphenyl­propiolates (3) were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…It is clearly indicated that n av values of the resulting PI films are higher than 1.6681 in the wavelength region of 500–700 nm. Indeed, these n av values exceed those of a few important commercially available optical plastics, such as polycarbonate ( n av = 1.581 at 632.8 nm) and polystyrene ( n av = 1.587 at 632.8 nm), as well as a few PVSs and PIs reported in the published literatures. , …”
Section: Resultsmentioning
confidence: 80%
“…It is clearly indicated that n av values of the resulting PI films are higher than 1.6681 in the wavelength region of 500–700 nm. Indeed, these n av values exceed those of a few important commercially available optical plastics, such as polycarbonate ( n av = 1.581 at 632.8 nm) and polystyrene ( n av = 1.587 at 632.8 nm), as well as a few PVSs and PIs reported in the published literatures. , …”
Section: Resultsmentioning
confidence: 80%
“…Furthermore, the Abbé number v D , modified Abbé number v D ′, and dispersion coefficients D and D ′ of the poly­(oxaselenolane)­s were calculated (Table S8), suggesting their low dispersion. In particular, the high modified Abbé number v D ′ of 251 and low dispersion coefficient D ′ of 0.004 of P 4 in the nonabsorbing wavelength range are superior to those of most of the polymer materials . Last but not least, the poly­(oxaselenolane)­s also enjoy admirable light transmittance.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The thiol−yne click reaction is supposed to be a useful strategy for multifunctionality and an efficient postsynthetic modification tool in chemistry because of its convenience, flexibility, and functionality resistance. 24 More importantly, thiol−yne click reaction can be performed via both nucleophile and radical-based pathways, creating a unique chance in modulating polymer properties with advanced features. 25 Owning to the abundant internal and terminal alkyne groups within the MONs' skeleton, thiol−yne click postmodification should be an additional and supplementary way to prepare multiple functionalized MONs.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of functionalized monomers to construct functionalized MONs is a feasible way, but the incorporation of the adequate abovementioned interaction sites within an MON is quite difficult at the current stage or impossible to a certain extent because of the limitation of versatile functionalized monomers. The thiol–yne click reaction is supposed to be a useful strategy for multifunctionality and an efficient postsynthetic modification tool in chemistry because of its convenience, flexibility, and functionality resistance . More importantly, thiol–yne click reaction can be performed via both nucleophile and radical-based pathways, creating a unique chance in modulating polymer properties with advanced features .…”
Section: Introductionmentioning
confidence: 99%